Analysis of Arabic Speaking Errors in PBA Student Presentation Activities of UIN Syahada Padangsidimpuan - Ira Aniati; Marisya Putri Diana; Hurriyatus Sa'adiyah (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2026)
Speaking skills (kalam) are an essential productive competence in Arabic language learning. This study aims to describe and analyze in-depth the oral Arabic language errors made by students of the Arabic Language Education (PBA) Study Program at UIN Syahada Padangsidimpuan during paper presentation activities. The main focus of the analysis is on linguistic errors covering phonological, morphological, syntactic, and translation aspects, with an emphasis on identifying mother tongue interference (Indonesian and local dialects) as one of the primary causal factors. This research employed a qualitative descriptive method. Data were collected through observation and note-taking techniques during students' oral presentations, which were then analyzed through the steps of error identification, classification, and explanation. The results indicate that phonological errors are dominant in the pronunciation of letters whose makhraj have no equivalent in the Indonesian language. Morphological errors were found in the use of tashrif (conjugation), plural forms, and gender markers. Syntactic errors included inaccuracies in i'rab (case endings), na'at-man'ut (adjective-noun) structures, and idhafah (genitive construction). Translation errors occurred due to improper diction and the transfer of sentence structures from the mother tongue. These findings imply the need for more contextual teaching strategies focused on contrastive analysis to minimize mother tongue interference and improve students' Arabic language accuracy.